Countermovement Jump Training Is More Effective Than Drop Jump Training in Enhancing Jump Height in Non-professional Female Volleyball Players - Ruffieux, Jan; Wälchli, Michael; Kim, Kyung-Min; Taube, Wolfgang (Frontiers in Physiology, 2020)
The aim of the present study was to compare the effects of countermovement jump (CMJ) and drop jump (DJ) training on the volleyball-specific jumping ability of non-professional female volleyball players. For that purpose, 26 female volleyball players (15-32 years) were assigned to either a CMJ or a DJ training group, which performed a six-week jump training (2 sessions per week, 60 jumps per session). Each group performed 20 % of the jumps in the jump type of the other group in order to allow the subjects to transfer improvements in explosive strength to the untrained jump type, thus minimizing the influence of coordination improvements. Before and after the training, jump height was assessed in four jump types, including the trained and volleyball-specific jump types. Although both training forms substantially improved jump height, the CMJ training was significantly more effective in all jump types (17 vs. 7 % on average; p < .001). This suggests that, at least for non-professional female volleyball players and a training duration of six weeks, training with a high percentage of CMJs is more effective than one with a high percentage of DJs. We hypothesize that this might be related to the slower stretch-shortening cycle during CMJs, which seems to be more specific for these players and tasks. Alternatively, technical deficiencies in the DJ technique might have hindered the subjects of the present study from fully benefitting from the greater training stimulus provided by DJs. These findings should support volleyball coaches in designing optimal jump trainings.